Seroprevalence of Antibodies to Brucella spp. and Neospora caninum in Cattle from Delta Region of Egypt: Correlation of Seropositivity with Abortion History - Ragab M. Fereig; Amira M. Mazeed; Azzah S. Alharbi; Mona Z. Abdelraheem; Mosaab A. Omar; Abdulaziz M. Almuzaini; Mohamed El-Diasty; Hend I. Elsharkawy; Kamel Sobhy; Caroline F. Frey; Gamal Wareth (Immuno)
Bovine brucellosis and neosporosis are reported as potential abortifacient infections in cattle worldwide. Brucellosis is additionally a zoonotic bacterial infection caused by numerous Brucella species. Meanwhile, neosporosis is a protozoan parasitic disease that is implicated in causing high economic losses in the cattle industry. Herein, we attempted to investigate the seroprevalence of specific antibodies to Brucella spp. and Neospora caninum using commercially available ELISAs. In addition, we conducted risk factor analysis and estimated the correlation of seropositivity of both pathogens with the recorded abortions in the tested herds. Serum samples from cattle (n = 460) collected from various governorates in the Delta region, northern Egypt, were targeted in this study. Overall, a seroprevalence of 5.4%, 33.3%, and 1.3% was revealed for Brucella spp., N. caninum, and mixed seropositivity, respectively. The location (Kafr El Sheikh vs. Dakahlia vs. Al-Qalyubiya vs. Damietta governorates) and a history of abortion (yes vs. no vs. unknown) were analyzed as risk factors of infection. Kafr El Sheikh governorate (57.7%, p = < 0.0001) and a history of abortion (54.1%, p = < 0.0001) were considered risk factors for Brucella spp. seropositivity compared to the reference factors Al-Qalyubiya (1.1%) and unknown abortion history (0.6%). In the case of N. caninum, the location was also considered a risk factor because the seropositive rates were significantly higher in Damietta (51%, p = 0.001) and Dakahlia (33.4%, p = 0.026) compared to Kafr El Sheikh (11.3%, set as a reference). Conversely to Brucella, animals without a history of abortion exhibited a higher seropositive rate for N. caninum (47.6%, p = 0.009) compared to those with a history of abortion (21.6%, set as reference). For further investigations into the association between abortion and the obtained seropositive rates, we also analyzed the reactivity by comparing samples of animals with, without, and unknown history of abortion. We detected high seroreactivity for Brucella spp. in samples collected from animals with a history of abortion, as demonstrated in the recorded antibody levels and correlation coefficient (Pearson r = 0.919). Based on our data, despite the higher seroprevalence of N. caninum compared to that of Brucella species, Brucella spp. might be the primary cause of abortion in our tested cattle population.